2017
DOI: 10.1111/jog.13296
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy and response time of dual biomarker model of insulin‐like growth factor binding protein‐1/ alpha fetoprotein (Amnioquick duo+) in comparison to placental alpha‐microglobulin‐1 test in diagnosis of premature rupture of membranes

Abstract: This is the largest study to date to reveal that Amnioquick duo+ and PAMG-1 have a comparatively high diagnostic accuracy in identifying women with PROM, with a concordance rate of 97.0%. The diagnostic response time of Amnioquick duo+ appears shorter. In equivocal cases, accuracy of Amnioquick duo+ was equal to that of the PAMG-1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 33 publications
(47 reference statements)
1
7
0
1
Order By: Relevance
“…23 Several factors have been considered to explain these conflicting results, including the detec- Although there are no data, including a cost-effectiveness analysis, supporting the use of AmnioQuick Duo+ instead of PAMG-1, a previous study has reported that AmnioQuick Duo+ has a faster response time. 14 In the present study, noninvasive assessment by AmnioQuick Duo+ accurately identified genuine PROM regardless of the duration of rupture or gestational age at rupture. AmnioQuick Duo+ also identified women with PROM who did not go on to deliver within the next 7 days.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…23 Several factors have been considered to explain these conflicting results, including the detec- Although there are no data, including a cost-effectiveness analysis, supporting the use of AmnioQuick Duo+ instead of PAMG-1, a previous study has reported that AmnioQuick Duo+ has a faster response time. 14 In the present study, noninvasive assessment by AmnioQuick Duo+ accurately identified genuine PROM regardless of the duration of rupture or gestational age at rupture. AmnioQuick Duo+ also identified women with PROM who did not go on to deliver within the next 7 days.…”
Section: Discussionsupporting
confidence: 51%
“…Although there are no data, including a cost‐effectiveness analysis, supporting the use of AmnioQuick Duo+ instead of PAMG‐1, a previous study has reported that AmnioQuick Duo+ has a faster response time . In the present study, noninvasive assessment by AmnioQuick Duo+ accurately identified genuine PROM regardless of the duration of rupture or gestational age at rupture.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…Gestational age was assessed according to the last menstrual period, PPROM was diagnosed by clinical standards using speculoscopy to assess amniotic fluid leakage from the cervix and then analyzed using Amnioquick ® , a quick test based on the detection of IGFBP-1 (insulin-like growth factor binding protein-1) in high concentrations in amniotic fluid, with a cut-off of 5 ng/mL to avoid interference with contaminants (semen, urine, or blood) [20]. Women with a proven diagnosis of PPROM were hospitalized and referred to our fetal medicine unit for further evaluation and treatment.…”
Section: Methodsmentioning
confidence: 99%
“…Few studies have performed a direct comparison simultaneously between the two immunochromatographic tests, as we did in the present study . With the aim of facilitating an understanding and comparative analysis with our research, we present these previous studies in detail in Table .…”
Section: Discussionmentioning
confidence: 99%